Unlocking export market potential with optimized coffee capsule packaging - Widyaningtyas, Shinta; Nanda, Ririn Fatma; Al Jabar, Andi; Pratama, Yogi; Febrianto, Dony; Hidayat, Muhammad Fajri (Universitas Muhammadiyah Magelang, 2025)
Coffee capsules, which are measured servings of premium, ready-to-brew ground coffee sealed to preserve flavor, possess significant development potential due to the limited number of competitors and promising export and domestic market opportunities. CV. Sundanika Indonesia is one such coffee capsule producer in Indonesia. In its export market initiation, CV. Sundanika Indonesia faced challenges in selecting the appropriate packaging material for its coffee capsules. This Community Service program aimed to facilitate the transition of coffee capsule packaging materials at CV. Sundanika Indonesia. The program commenced with discussions to comprehensively identify the partner's problems and provide recommended solutions. The methods employed included Focus Group Discussions, the provision of sample coffee capsule packaging, and program evaluation. The program results indicate that the partner gained an understanding of packaging functions in general and the significant differences between plastic and aluminum foil packaging for coffee capsules, which motivated them to switch to aluminum foil packaging. A 30% increase in the partner's understanding supports the success of this packaging transition.